INNOVATIVE TECHNOLOGIES IN TRANSLATION («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article analyses the usage of the newest informational technologies in the field of translation. The article examines broadly available informational technologies, which are meant to improve the efficiency of the translation process and help the translator. Particular attention is given to the most progressive programs for translation, based on neural network and cloud storage technologies.
Keywords: informational technologies; translation; translator; machine translation.